التجربتين العُمانية والماليزية في إدارة الوثائق والمحفوظات: دراسة مقارنة: THE OMANI AND MALAYSIAN EXPERIENCES IN RECORDS MANAGEMENT AND ARCHIVES: A COMPARATIVE STUDY - AlRashdi , Sulaiman Saleh Said; Lubis, Asmuliadi; Mansor, Fadillah (Online Journal of Islamic Management and Finance (OJIMF), 2023)
This article aims to provide a forward-looking vision by comparing the Omani and Malaysian experiences in records management and archives, and highlighting the common aspects between them despite the time difference in their establishment. The problem of the study can be formulated in the following question: What are the similarities and differences between the Omani and Malaysian experiences in records management and archives? The study seeks to highlight the importance of investing in the similarities between the two experiences in order to serve workers and specialists in the field in particular, and the field of records and archive management in general. The study relies on the survey methodology by examining the two experiences and describing each experience through several points represented in origin, international standards, and electronic management of records, regional branches, and attention to oral history, private documents, conferences and exhibitions. The study community consists of the authority responsible for supervising this field in both countries, as the National Records and Archives Authority represents the authority responsible for supervising the system in the Sultanate of Oman and the Malaysian National Archives in the Federal Kingdom of Malaysia. Among the most prominent findings of the article: There is a great similarity between the two experiences in many aspects, despite the old Malaysian experience in the management of records and archives.